(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This scientific article discusses the role of human capital and digital competencies in increasing labor productivity in the digital economy based on in-depth theoretical and practical analysis. The main goal of the study is to identify the qualitative changes in human capital in the process of digital transformation and the mechanisms of its impact on labor productivity. The study studies the impact of digital competencies on economic efficiency based on modern economic theories, including the knowledge economy, human capital theory, and the Industry 4.0 concept. The results of the study show that employees with advanced digital competencies can increase labor productivity by 40–60 percent. At the same time, the lack of digital competencies in developing countries is one of the main factors limiting economic growth. At the end of the study, a comprehensive model of human capital development is proposed and its practical significance is substantiated.